2020
DOI: 10.29333/ejmste/8474
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Students’ Readiness to Transition to Emergency Online Learning in Response to COVID-19: Case of Qatar

Abstract: This study examined engineering students' initial readiness to transition to emergency online learning in response to COVID-19 in Qatar. A theoretical framework is proposed for understanding the factors influencing students' readiness for change. Sequential explanatory mixed-method research was conducted, with 140 participants completing an online survey, of which 68 also contributed written reflections and 8 participated in semi-structured interviews. Exploratory factor analysis displayed a four-factor struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“…As reported by Chiu and Chai (2020) [43], university leaders should consider the instructor's perspective, allowing them to better plan and motivating them to reduce unnecessary tasks that cause stress to both students and lecturers themselves. Previous studies reported that skilled supportive instructors and leaders are vital to cultivating motivation and self-efficacy among students [47,87]. Doing so will establish online learning environments that support active learning and student readiness for online learning [88][89][90].…”
Section: University Supportmentioning
confidence: 98%
See 3 more Smart Citations
“…As reported by Chiu and Chai (2020) [43], university leaders should consider the instructor's perspective, allowing them to better plan and motivating them to reduce unnecessary tasks that cause stress to both students and lecturers themselves. Previous studies reported that skilled supportive instructors and leaders are vital to cultivating motivation and self-efficacy among students [47,87]. Doing so will establish online learning environments that support active learning and student readiness for online learning [88][89][90].…”
Section: University Supportmentioning
confidence: 98%
“…As reported by Bandura (1995), competence is assumed to be associated with self-efficacy [48]. In this regard, individuals who perform ineffectively do not do so due to a lack of skills or knowledge but because they lack the self-efficacy to practice these skills and knowledge effectively [46,47]. In this subsection, we concluded that student's self-efficacy is an essential contributor to their sustainable wellbeing, as reported in previous studies which deemed self-efficacy as significant for academic success [49].…”
Section: Self-efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…The author sees the benefits of online education and suggests that it should be continued after the COVID lockdown. K. Naji et al (2020) report their experience with the COVID-based transition for engineering students in Qatar, listing effective communication, proper pedagogical mode (e.g., student group projects), interactive mode of instruction, and availability of early assistance for students who struggle as the critical factors to overcome the problems with the online course transitions in response to COVID-19. Pradeep Sahu (2020) and P. Hiremath et al (2020) address the impact of COVID on the mental health and economic conditions of the students.…”
Section: Introductionmentioning
confidence: 99%